The Accuracy of Balance Model in Predicting Stock Investment During The Covid-19 Pandemic on LQ 45 Index - Elly Susanti; Nelly Ervina; Ernest Grace; Sudung Simatupang (Universitas Winaya Mukti, 2021)
In doing investment, an investor certainly avoids risk; thus, the investor needs a model in making predictions to forecast the return of shares. There are two models to predict this: Capital Asset Pricing Capital (CAPM) and Arbitrage Pricing Theory (APT). The purpose of this study is to find out which models are more accurate in determining investment options, especially during the Covid-19 pandemic in companies that are included in the LQ 45 Index group. The population in this study is 50 companies listed in LQ 45 from February 2020 - July 2021. The sampling technique used in this study is purposive sampling. The data used in this study will be processed through Ms.Excel and SPSS Version 21. The data analysis techniques used in this study are the Basic Assumption Test consisting of Normality Test and Homogeneity Test, Mean Absolute Deviation (MAD), and hypothesis testing consisting of independent t-test samples. The results in this study show that Model is accurate in predicting stock returns in the Covid-19 pandemic is a CAPM model this is because the value of MAD CAPM is smaller than mad APT. Furthermore, independent t-test samples showed that H0 was rejected which meant that there was a difference in accuracy between CAPM and APT in calculating the return of LQ 45 shares. The implication of this study are expected to provide references to investors and potential investors as a source of information in decision making to make investments in this pandemic period.